Analysis, design and simulation of single-phase power supply for rotor excitation of aircraft starter/generator - Xing, Da (2016)
The demand of electrical power increases rapidly in the new designs of military and civil aircrafts due to its better performance, less maintenance, less weight and high efficiency. To meet this growing demand of electrical power, engine coupled starter/generators coupled with power electronics supplies are being used to the on-board electrical power systems. AC excitation system from the DC bus voltage is applied to excite the rotor of starter/generator. The main objective of this final year project is to analyze, design and simulate a power electronic supply for rotor excitation of aircraft generator from the aircraft DC bus, which inverts a 270 V DC voltage to a stable high-quality 500 V 400 Hz single-phase AC voltage with a 4 kVA 0.8 power factor (p.f) lagging output load. To achieve this objective, at the first step, a single-phase supply consisting of a boost converter and a single-phase full bridge inverter was proposed. The boost converter provides the single-phase voltage source inverter (VSI) with desired and stable input DC voltage and strengthen the fault tolerant ability of the excitation system. And the single-phase VSI converts and regulates the DC voltage to desired AC voltage. Secondly, the author investigated and analyzed the boost converter and single-phase full bridge inverter, and developed control strategies including Sinusoidal Pulse Width Modulation (SPWM), Proportional-Integral (PI) control and DQ frame control. At the third stage, the author designed and simulated the proposed supply with closed-loop control system using MATLAB Siumlink. The feedback control of the boost converter used PI control and PWM, while, DQ frame control and SPWM have been applied to the closed-loop system of the single-phase VSI. The simulation results show that the designed supply is able to invert a 270 V DC voltage varying between 250 V to 350 V to a 500 V 400 Hz single-phase AC voltage. Meanwhile, the designed closed-loop control system has the ability to give a fast response to any change of the output load or input voltage within a wide range and regulate the output AC voltage at desired value with very low total harmonic distortion (THD). The simulation results are consistent with those from circuits analysis.